2011
DOI: 10.1111/j.1748-3743.2010.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing for older people in nursing homes: a review of the key issues

Abstract: Prescribing of medication is one of the most common interventions that residents in nursing homes will experience. There is little doubt that medication has greatly contributed to improvements in symptom control, long-term management of medical conditions and greater longevity. However, the quality of prescribing has also been criticised and this paper outlines the issues that have proved to be most problematic and have been repeatedly highlighted in the literature. There have been numerous reports of over-use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 114 publications
0
26
0
Order By: Relevance
“…An age-associated reduction in physiological capacity alongside an increased prevalence of multimorbidity and polypharmacy contribute to the complexities of prescribing in older adults [23]. Prescribing interventions are the most common interventions that take place in care homes and often target inappropriate prescribing (under-, over-, or mis-prescribing), adverse events and compliance [24], and commonly aim to ‘optimise’ the use of medicines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An age-associated reduction in physiological capacity alongside an increased prevalence of multimorbidity and polypharmacy contribute to the complexities of prescribing in older adults [23]. Prescribing interventions are the most common interventions that take place in care homes and often target inappropriate prescribing (under-, over-, or mis-prescribing), adverse events and compliance [24], and commonly aim to ‘optimise’ the use of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the factors contributing to all aspects of poor medicines use in care homes are polypharmacy (care home residents are prescribed an average of eight medicines), inappropriate prescribing, inadequate communication and handover protocols between staff, interruptions during drug rounds, inadequate communication across the various healthcare interfaces’ and the lack of clear responsibility for the review of patients’ medicines [24]. To illustrate further, Loganathan and colleagues’ systematic review [20] of interventions to optimise prescribing in care homes reported heterogeneity in outcomes, hindering the development of firm conclusions and recommendations for practice.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce preventable harm, safe prescribing in aged care facilities requires consideration of residents’ total needs in order to mitigate cognitive and functional deterioration 1–3. Various studies exploring prescribing safety in long-term aged care facilities report a higher rate of prescribing errors compared with hospitals 7 13 14. Australian long-term aged care facilities also report a high incidence of polypharmacy with residents averaging seven to ten medications each 15 16.…”
Section: Introductionmentioning
confidence: 99%
“…Due to ageing, shorter hospital stays and an emphasis on outpatient care, the number of older persons receiving home healthcare is growing [4] . Therefore, Drug Related Problems (DRPs) are an increasing challenge in homecare organizations as described by Meredith et al [5] and Parsons et al [6] .…”
Section: Introductionmentioning
confidence: 99%